1993
DOI: 10.2307/3502379
|View full text |Cite
|
Sign up to set email alerts
|

" Be Quiet ", mais modérément: Le rôle de l'État dans la pensée économique de Jeremy Bentham

Abstract: Be quiet », but keep cool : the role of the state in jeremy bentham's economic thought. This paper aims at showing that the tradition which uses to connect Bentham's utilitarianism with economie liberalism neglects the peculiarity of an approach for which economics is by no way autonomous to legislation. In this respect, we must underline the importance of information problems. Although they justify the non-intervention of the State, as long as we only consider the economie ends-« subsistence » and « abondance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Recent research into Bentham's economics has shown that this was an oversimplified picture. 16 But the plain fact remains that the sphere of agenda, each of which involves the legislator's manipulating some individual interests, is wide in Bentham's view, whatever the stage of his intellectual career.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research into Bentham's economics has shown that this was an oversimplified picture. 16 But the plain fact remains that the sphere of agenda, each of which involves the legislator's manipulating some individual interests, is wide in Bentham's view, whatever the stage of his intellectual career.…”
Section: Discussionmentioning
confidence: 99%
“…17 See Sigot (1993) among others. 18 On this, see Sigot (1993Sigot ( , 2001. 19 'It should not be forgotten than political economy was for Bentham a branch of the science of legislation' (Guidi 2004: 176).…”
Section: Individual Interests and Collective Interest In Bentham's Workmentioning
confidence: 96%
“…See also the position of Friedman (1953), who points out Bentham's 'refusal to see the reality of conflict between the individual interest and that of the community '. 1904); the distinction between the economic and the politic domain (Halévy 1901a, Sigot 2001; the role of State (Sigot 1993); the individual and the collective aspect of the utility principle (Sigot 1993(Sigot , 2001; the distinction between a moral utility function and a personal utility function (Harsanyi 1955(Harsanyi , 1992; the issue of laundering preferences (Goodin 1986); or, more generally, the choice of a model of utility suited to the ethical project (Haslett 1990, Broome 1994. Nevertheless, if all of these positions establish -or negate -the existence of a contradiction, none of them confronts the persistence of such an opposition.…”
mentioning
confidence: 99%
“…Whereas individual agents act according to what they believe to be their optimal trajectories, the Benthamite legislator aims at taking into account what optimal trajectories would be in case of perfect knowledge of the tastes, and compares them to the actual behaviour of the individuals. This helps explain the reasons why Benthamite economics is, from the beginning, public economics: public intervention is, of course, required in order to provide adequate information, to make up for external effects and coordination failures (see Sigot 1993); but it is also required to ensure the internal consistency of each individual -that is, the consistency between his tastes and his resulting choices.…”
Section: The Time Of Assessment: What Does It Mean Being a Bad Calcumentioning
confidence: 97%